Measuring Effects of Demographic Variables on Health Services Utilization - Reinke, William A. (1967)
To predict demands for health services, planners must measure the impact of demographic change. This article presents a new method, the multi-sort technique, to improve analysis of the effects of multiple demographic variables. The technique is demonstrated in an analysis of the changing demand for physicians' services in Taiwan. Multiple regression techniques, including those that utilize dummy variables, have been used to analyze effects of demographic variables, but interactions may be overlooked entirely or inadequately identified. Analysis of variance has proved useful in handling interactions, but uneven distribution of observations among cells creates orthogonality problems. The multi-sort technique is an approximation procedure that simplifies computations while maintaining the analysis of variance approach. The procedure assigns cell weights in all evaluations according to the rules for evaluating main effects; thus the assessment of interactions is approximate but not tedious. Comparison of computer results obtained by the new technique with those from certain multiple regression procedures indicates that the multi-sort technique offers more promise in the evaluation of demographic data than previous applications of analysis of variance would indicate. The study also gives practical suggestions for combining various techniques in a total analysis. The Taiwanese data in this paper were obtained from a survey supported by The Agency for International Development.